ANALISIS KEBIJAKAN KESELAMATAN PASIEN DI INSTALASI RAWAT INAP RUMAH SAKIT UMUM DAERAH ARIFIN ACHMAD PROVINSI RIAU - Handoko, Bobi; Fristasya, Andra; Firdaus, Muhammad; Mutiara, Sherly (LPPM Universitas Awal Bros, 2023)
Patient safety is an important element to improve the quality of health services in the hospital. Patient safety is a system that makes patient care safer, including risk assessment, identification and management of patient risks, reporting and analysis of incidents, the ability to learn from incidents and follow-up, as well as implementing solutions to minimize risks and prevent injuries caused by errors resulting from carrying out an action or not taking action that should be taken The results of this research are the process in this research of Patient Safety Policy Analysis In the Inpatient Installation of the Arifin Achmad Regional General Hospital, Riau Province, in the reception of outpatients, the six patient safety targets at the Arifin Achmad regional general hospital have been implemented quite well, the implementation of the six patient safety targets is also carried out well in the treatment room. Ianp and polyclinics, however, several interviews with patients showed that the patient safety targets carried out in hospitals have not been fully met because there are still deficiencies such as a lack of effective communication methods with patients and are not in accordance with the procedures. This study aims to find out about Patient Safety Policy Analysis at the inpatient insrallation at the Arifin Achmad Regional General Hospital, Riau Province. This type of research in qualitative with an analytic descriptive approach. This research was conducted on 9 February - 30 June 2023 at Arifin Achmad Hospital, Riau Province. There are 5 informants in this study and this research uses the Content Analysis model.